The Psychological Impact of COVID-19 on Healthcare Workers in Saudi Arabia: A Year Later Into the Pandemic - Almalki, Atiah H.; Alzahrani, Mohammad S.; Alshehri, Fahad S.; Alharbi, Adnan; Alkhudaydi, Samirah F.; Alshahrani, Rawan S.; Alzaidi, Aseel H.; Algarni, Majed A.; Alsaab, Hashem O.; Alatawi, Yasser; Althobaiti, Yusuf S.; Bamaga, Ahmed K.; et al. (Frontiers in Psychiatry, 2021)
Objective: The COVID-19 pandemic poses unprecedented challenges to healthcare workers worldwide. This study sought to estimate the prevalence of depression, anxiety, and stress among healthcare workers in Saudi Arabia, and to identify the factors associated with these psychological disorders. Methods: A cross-sectional questionnaire-based study was conducted from January 21 to March 2, 2021. Physicians, pharmacists, nurses, and other healthcare workers from different parts of Saudi Arabia were recruited through snowball sampling. Psychological outcomes were measured using the Depression, Anxiety, and Stress Scale (DASS-21). Pearson’s chi-square test was used to explore the bivariate association between diverse characteristics and each outcome. Multiple logistic regression analyses were performed to identify factors associated with depression, anxiety, and stress. Results: A total of 501 healthcare workers completed the survey, of whom 60% were female and nearly half were pharmacists. The majority (76.25%) of respondents reported that a family member, friend, or colleague had contracted COVID-19, and more than one-third (36%) knew someone who died due to COVID-19. Overall, the estimated prevalence rates of depression, anxiety, and stress were 54.69%, 60.88%, and 41.92%, respectively. The multivariate analysis revealed that healthcare workers with chronic diseases, nurses, and healthcare workers from the southern region were more likely to suffer from depression and stress. Further, individuals with positive COVID-19 test results showed a greater proportion of depressive symptoms compared to others. In addition, knowing someone who died due to COVID-19 and having a chronic illness were predisposing factors for anxiety. Conclusion: After more than a year, the prevalence of depression, anxiety, and stress remains substantial among healthcare workers in Saudi Arabia. The findings can help guide efforts to mitigate the psychological impact of the pandemic.